Bridging the policy-practice divide: global systematic mapping of circular economy implementation in construction waste - Al Kaabi, Mohammed; Abdella, Galal M.; Gunduz, Murat (Frontiers in Built Environment, 2025)
The construction industry generates over one-third of global waste and consumes 36% of global energy, highlighting the urgent need for a circular economy transition. Despite increasing government intervention, a persistent gap exists between policy development and operational implementation in construction and demolition waste (CDW) management. This systematic mapping study analyzed 1,842 high-relevance papers (2015-2025) selected from 5,417 publications to assess government-driven circular economy transitions. Advanced analytical methods appear in 32.4% of studies. However, only 12% provide validated tools for real-world policy deployment, exposing a stark implementation deficit. Geographic analysis reveals imbalances: policy-leading economies (China 28.4%, EU 31.8%, US 16.7%) dominate research, while high-waste countries like Brazil and India (3.7%) remain underrepresented. Economic policy instruments and cross-jurisdictional coordination mechanisms exhibit the largest research-practice gaps. We identify three critical priorities: mathematical optimization models for policy calibration, frameworks tailored to developing contexts, and coordination mechanisms for multi-stakeholder governance. This study proposes a tiered research agenda addressing both immediate operational needs and long-term systemic integration. The methodology offers a replicable approach for systematically identifying research-practice translation gaps and prioritizing implementation-focused research directions in sustainability policy domains.